(untitled) (University of Khartoum Journal of Agricultural Sciences, 2023)
Biodegradation of pendimethalin by three strains of bacteria viz; Pseudomonas aeruginosa, Bacillus mycoides and Bacillus cereus isolated from pesticides polluted soil was studied in mineral salt medium. Pendimethalin was incubated with each of the three strains of bacteria and samples were drawn at 0, 3, 7, 15 and 30 days for gas chromatographic analysis. The loss in the initial concentration (400 ppm) over time was monitored and used to compute the half lives following a biphasic model. GC-MS was used to identify the major metabolites as well as to re- confirm the identity of the starting material (pendimethalin). The results showed that the remaining amounts of pendimethalin recovered from media inoculated with Pseudomonas aeruginosa for 3, 7, 15 and 30 days were; 75.5%, 69.25%, 29.75 % and 19.25% respectively, While the amounts recovered from media inoculated with Bacillus mycoides were; 48.75%, 46.25%, 39.25 % and 28.25% following the same order. On the other hand, the respective amounts recovered from media inoculated with Bacillus cereus were; 45 %, 32.5 %, 30.5 % and 19.75% at 3, 7, 15 and 30 days, respectively. Despite the significant drop in the starting material, no metabolites were detected in Bacillus cultures while only N-(1- ethylpropyl)-3-methyl-2, 6-diaminobenzine was detected in P. aeruginosa culture indicating the capability of these microorganisms of complete mineralization of pendimethalin. Pendimethalin biodegradation by the three types of bacteria followed a biphasic model with faster rate of